Ecology and natural history of swimming pitcher mites (Creutzeria spp., Histiostomatidae) from the traps of Nepenthes pitcher plants. (13th August 2019) - Lam, W. N.; Ling, J.; Lum, T. Q. H.; Tan, H. T. W.
Abstract: Pitcher plants of the genus Nepenthes trap and digest invertebrate prey to supplement their nutrient requirements using fluid‐containing, modified leaves known as 'pitchers'. Pitchers are habitats to many aquatic metazoan and microbial species known as 'inquilines'. Mites (Histiostomatidae) are a common but poorly studied inquiline taxon – little is known of their life cycles and their interactions with other inquiline taxa. The objectives of this study were to (1) investigate interspecific interactions between inquiline Creutzeria mites, microbes and Endonepenthia schuitemakeri (Diptera: Phoridae) (2) quantify the net nutritional benefit of Creutzeria mites and other inquilines on Nepenthes gracilis nitrogen sequestration and (3) determine if E. schuitemakeri can act as dispersal agents for Creutzeria mites. In the first part of the study, Creutzeria mites were reared in vitro under simulated pitcher conditions for varying lengths of time. Their populations were found to increase exponentially with time, peaking 24.2 days into the experiment and decreasing thereafter. In the second experiment, in vitro experiments were established with different combinations of E. schuitemakeri larvae, ant prey biomass, ant prey species and Creutzeria mite addition. Mite population, fluid microbe density and total pitcher‐available nitrogen were measured at the end of 24 days as determined in the first part of the study. Confirmatory path analyses suggested that Creutzeria mites competed with microbes for prey resources (negative effect of microbe density on mite population) were not facilitated by E. schuitemakeri (no effect of E. schuitemakeri on mite population) and had a neutral to negative effect on pitcher nutrient sequestration (weak negative effect of mite population on pitcher‐available nitrogen). However, Creutzeria deutonymphs could not be found on any of the E. schuitemakeri adults emerged during the experiments, suggesting these utilize other inquiline species as dispersal agents, or require environmental/stress trigger factors to form deutonymphs. Abstract : Pitcher plants of the genus Nepenthes trap and digest invertebrate prey to supplement their nutrient requirements using fluid‐containing, modified leaves known as 'pitchers'. Pitchers are habitats to many aquatic metazoan and microbial species known as 'inquilines'. In vitro experiments were used to examine the relationships between ubiquitous but poorly studied Creutzeria mites and their pitcher plant host, and with other pitcher inhabitants. Creutzeria mites were found to have a negligible effect on pitcher nutrient availability and appeared to compete with fluid microbes for prey resources. Creutzeria mites are likely to depend on other inhabitants as dispersal agents, but we did not find any evidence for their utilization of emerging scuttle fly adults for this purpose.